Implementation of School Principal’s Managerial Competence in Improving School Quality - Kusmiyanto, Bambang; Setianingsih, Ety; Prasetya, Prasetya; Nuryani, Lilis Kholisoh; Herman, Maman (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2025)
This study aims to analyse the implementation of principals' managerial competencies, which include conceptual, humanistic, and technical skills, in improving the quality of education in schools. A qualitative approach, employing descriptive methods, was used to examine the problems and gain deeper insights. Data collection techniques included interviews, observations, and documentation studies. Data were analysed through data reduction, data presentation, and conclusion drawing/verification. The study findings indicate that principals excel in coordinating policies, solving problems collaboratively, and developing structured plans, which have a positive impact on school operations. Humanistic skills, including communication, empathy, and teacher motivation, foster a supportive and productive environment. Principals' technical skills in curriculum development, classroom supervision, and administrative management contribute to school operational efficiency. This study suggests that principals who combine strong leadership with emotional intelligence and technical expertise create a conducive learning environment. This study contributes to educational leadership by offering practical insights for school administrators and recommends a focus on continuous professional development for principals to enhance their competencies.